Factors Affecting Cloud-Based Accounting Adoption in the Indonesian Banking Sector - Ryandika Ramadhan Al Farishi; Lauw Tjun Tjun (Jurnal Akuntansi, 2025)
This study aims to analyse the factors influencing the adoption of cloud-based accounting in the Indonesian banking sector. The sample size in this study was 80 respondents of Indonesian banking employees who implemented cloud-based accounting through Google Forms. The data was processed using SmartPLS 4 with SEM-PLS analysis. The results showed that human and organisational factors significantly affect the adoption of cloud-based accounting. On the other hand, technological, environmental, and perceived trust factors are insignificant to adopting cloud-based accounting. This study can contribute to human and organisational factors that can influence developments in the application of cloud-based accounting in the banking sector. In contrast, technological and environmental factors must be considered by banks and the Indonesian government, especially clarity regarding data security protection from cloud adoption to provide confidence to users of cloud-based accounting applications.